Rehabilitation of abandoned housing project by purchasers in Peninsular Malaysia: Problems and challenges - Md Dahlan, Nuarrual Hilal (2009)
Abandoned housing projects are pathetic phenomena occurring in housing industry in Peninsular Malaysia.Considerable housing projects have been identified as being abandoned and have shuddered to a halt.There are several methods to rehabilitate abandoned housing projects.One of these is the rehabilitation carried out by purchasers.The paper entitles as to the above, will be based on documentations and archival records of qualitative case study in nature, through a legal perspective, intends to explore and penetrate the legal phenomena and problems in the rehabilitation of an abandoned housing project in Peninsular Malaysia, through the initiative of purchasers. From this paper it is hoped that certain findings in regard to their legal problems of the said project could be identified and legal approaches toward their rehabilitations can be established in the said housing project for future guidelines and suggestions to overcome the same, if similar case were to happen. These will hopefully, to some extent, assist the authorities concerned (such as the Ministry of Housing and Local Government, local authorities, developer and financiers) to adopt legal policies and take certain legal measures to rehabilitate abandoned housing projects in Peninsular Malaysia.